Transforming Islamic Education: Curriculum Changes at Pesantren Al-Mukmin Ngruki Over Five Decades - Muhammad Luthfie Ramadhani Suprapto; Suhendri Suhendri; Rahmat Hidayat; Vina Annisa (Institut Agama Islam Negeri Lhokseumawe, 2025)
Pesantren Al-Mukmin Ngruki was established to educate students and shape them into a generation of Muslims who are ready to accept and practice Islam in its entirety (kaffah). However, Pesantren Al-Mukmin Ngruki is often labeled as a radical pesantren that teaches exclusive and intolerant religious beliefs, especially after the 2002 Bali bombing. The negative stigmas associated with this pesantren have caused issues for its organizers, especially since the institution is often linked to its founders. The negative accusations published by the media have also been highlighted by various parties on various occasions. Pesantren Al-Mukmin Ngruki’s curriculum has been accused of teaching terrorism and bomb assembly, and is still often labeled as a radical pesantren that produces terrorists. Therefore, this study will investigate the curriculum dynamics of Pesantren Al-Mukmin Ngruki to determine whether these accusations are supported by evidence. The researchers employed a qualitative research method with a historical approach, which contains four steps: heuristics, criticism, interpretation, and historiography. The results of this study reveal that the curriculum at Pesantren Al-Mukmin Ngruki is an integrated curriculum that combines the national curriculum from the Ministry of Education, Culture, Research, and Technology, with the pesantren curriculum. This curriculum aims to produce Muslim scholars and intellectuals, with a focus on Islamic religious education followed by general knowledge, science, and technology.